Samsung Galaxy Tab 10.1 for dummies - Gookin, Dan. (For Dummies, 2012)
"Learn to: Navigate the Galaxy Tab and download apps, movies, and music at blazing 4G LTE speeds; Video chat and read eBooks on the bigger, better screen; E-mail, browse the web, and map directions for a trip"--Cover.